2022
DOI: 10.1136/jitc-2021-004400
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 blockade restores CAR T cell activity through IFN-γ-regulation of CD163+ M2 macrophages

Abstract: BackgroundThe immune suppressive tumor microenvironment (TME) that inhibits T cell infiltration, survival, and antitumor activity has posed a major challenge for developing effective immunotherapies for solid tumors. Chimeric antigen receptor (CAR)-engineered T cell therapy has shown unprecedented clinical response in treating patients with hematological malignancies, and intense investigation is underway to achieve similar responses with solid tumors. Immunologically cold tumors, including prostate cancers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…We and others have demonstrated that PD-1/PD-L1 blockade, regardless of the technique used, can enhance CAR-T cell activity and rescue exhausted CAR-T cells in preclinical experiments. 21 , 37 , 38 , 39 Nevertheless, the clinical results were inconsistent. On one hand, Adusumilli et al.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that PD-1/PD-L1 blockade, regardless of the technique used, can enhance CAR-T cell activity and rescue exhausted CAR-T cells in preclinical experiments. 21 , 37 , 38 , 39 Nevertheless, the clinical results were inconsistent. On one hand, Adusumilli et al.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating preclinical evidence indicates that the efficacy of autologous cell therapies such as DC vaccines but also CAR-T cell therapies could be further improved by concomitant PD-L1-targeted immune checkpoint inhibition to counteract the establishment of an immunosuppressive macrophage niche. 8 …”
Section: Main Textmentioning
confidence: 99%
“…found that M2-type TAMs in TME induced CAR-T to overexpress PD-1, thereby affecting the PD-1/PD-L1 pathway to reduce the activity of CAR-T cells. Besides, the use of atezolizumab (a PD-L1 inhibitor) led to M2-type TAMs apoptosis, which improved the anti-tumor activity of CAR-T cells ( 78 ). Therefore, ICIs not only block the PD-1/PD-L1 axis to enhance CAR-T cell function, but also improve the immune microenvironment and reduce CAR-T cell exhaustion ( 79 81 ).…”
Section: Car-t Cells Exhaustionmentioning
confidence: 99%